Acute Ascending Thrombosis of Abdominal and Suprarenal Aorta. (7th October 2014) - Robaldo, Alessandro; Pagliari, Stefano; Colotto, Patrizio
Abstract : We report the diagnostic and successful therapeutic images of an acute occlusion of the abdominal and suprarenal aorta. This lesion is a rare but catastrophic pathology which can cause severe ischemic manifestations, depending on the site of obstruction, with high rate of mortality even after treatment. In the majority of cases it represents a surgical emergency. Although the mechanism of the thrombosis has not been delineated, the proposed etiologies include propagation of thrombus from distal artery occlusion, cardiac thromboembolism, dislodgment of a mural thrombus, or coagulation disorders. Frequent risk factors include advanced atherosclerosis combined with a low flow state because of poor cardiac performance. The management of this condition includes immediate intervention with systemic heparinization, improvement of the cardiac condition, and surgical revascularization based on the clinical and anatomical presentation. In this case the authors highlight the importance of an early detection and early intervention to enhance survival rates and reduce morbidity.